NEXUS trial: a multicenter phase II clinical study evaluating the efficacy and safety of the perioperative use of encorafenib, binimetinib, and cetuximab in patients with previously untreated surgically resectable BRAF V600E mutant colorectal oligometastases - Shin Kobayashi; Hideaki Bando; Akinobu Taketomi; Takeshi Takamoto; Eiji Shinozaki; Manabu Shiozawa; Hiroki Hara; Kentaro Yamazaki; Koji Komori; Nobuhisa Matsuhashi; Takeshi Kato; Yoshinori Kagawa; et al. (BMC Cancer, 2023)
Abstract Background The optimal treatment strategy for resectable BRAF V600E mutant colorectal oligometastases (CRM) has not been established due to the rarity and rapid progression of the disease. Since the unresectable recurrence rate is high, development of novel perioperative therapies are warranted. On December 2020, the BEACON CRC triplet regimen of encorafenib, binimetinib, and cetuximab was approved for unresectable metastatic colorectal cancer in Japan. Methods The NEXUS trial is a multicenter phase II clinical study evaluating the efficacy and safety of the perioperative use of encorafenib, binimetinib, and cetuximab in patients with previously untreated surgically resectable BRAF V600E mutant CRM. The key inclusion criteria are as follows: histologically diagnosed with colorectal adeno/adenosquamous carcinoma; RAS wild-type and BRAF V600E mutation by tissue or blood; and previously untreated resectable distant metastases. The triplet regimen (encorafenib: 300 mg daily; binimetinib: 45 mg twice daily; cetuximab: 400 mg/m2, then 250 mg/m2 weekly, 28 days/cycle) is administered for 3 cycles each before and after curative resection. The primary endpoint of the study is the 1-year progression-free survival (PFS) rate and the secondary end points are the PFS, disease-free survival, overall survival, and objective response rate. The sample size is 32 patients. Endpoints in the NEXUS trial as well as integrated analysis with the nationwide registry data will be considered for seeking regulatory approval for the perioperative use of the triplet regimen. Discussion The use of the triplet regimen in the perioperative period is expected to be safe and effective in patients with resectable BRAF V600E mutant CRM. Trial registration jRCT2031220025, April. 16, 2022.